Ceria-zirconia mixed oxides as thermal resistant catalysts for the decomposition of nitrous oxide at high temperature - Esteves, P.; Wu, Y.; Dujardin, Christophe; Dongare, Mohan K.; Granger, P. (Catalysis Today, 2011)
This present study deals with the development of thermally stable catalysts for the decomposition of nitrous oxide. There is actually a growing interest to minimise the emissions of nitrous oxide (N(2)O) as side-product from nitric acid plants due to a global warming potential of approximately 300 times higher than that of CO(2). Different strategies have already been implemented at industrial scale but they are still suffering from significant drawbacks essentially associated to a poor selectivity and sometimes a short lifetime in particular when the catalytic process is inserted downstream the ammonia burner. In those critical conditions, with high residual temperature of similar to 900 degrees C, significant surface and bulk reconstructions take place and then lead to drastic losses of specific surface area and related catalytic performances in the decomposition of N(2)O to N(2). Previous investigations performed in our laboratory revealed the potentiality of zirconia particularly after yttria incorporation [Appl. Catal. B 62 (2005) 236]. Novel developments of more stable ceria-zirconia based catalysts are reported in this study. Further stabilisation and enhancement in activity have been discussed on the basis of oxygen mobility related to structural properties. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceria-zirconia based catalysts; Greenhouse gas; N(2)O catalytic decomposition; Nitric acid plant; Nitrous oxide